Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Usaha Tani Jagung Di Desa Ntonggu Kecamatan Palibelo Kabupaten Bima (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
Corn is one of the world's most important food crops besides wheat and rice. Aside from being a source of carbohydrates, corn is also grown as animal feed. Corn farming is a business developed by the community in Ntonggu Village, Palibelo District, Bima Regency, so that it becomes the main commodity when summer arrives. Scarcity of fertilizers and pesticide costs, seed costs and labor wages that often increase every year are obstacles for corn farmers. The purpose of this study was to determine the effect of production factors (land area, cost of fertilizer, cost of pesticides, cost of seeds, number of workers, output prices and labor wages) on the income of corn farming and to determine the feasibility of corn farming in Ntonggu Village, Palibelo District, Bima Regency. The data used were obtained from observations and interviews with 35 respondents, the sampling technique used was purposive sampling method. The method used in this study is multiple linear regression and using the B/C ratio. The results showed that the factors affecting the income of corn farming in Ntonggu Village, Palibelo District, Bima Regency were the Factors of Land Area (X1), Number of Labor (X5) and Labor Wages (X7) and Based on the results of the analysis of income and feasibility of corn farming in Ntonggu Village, Palibelo District, Bima Regency, the average income of respondents was Rp. 11,673,773 of the total cost of Rp. 4,747,286. The feasibility analysis shows that the B/C ratio is 1.5 so that corn farming in Ntonggu Village, Palibelo District, Bima Regency is profitable and feasible.